A Comparison of The Incidence of Coronary Heart Disease In Police Based In Urban And Rural Areas: A Study of East Java Regional Police - Iwana Anny Rakhmawati; Bagus Putra Dharma Khrisna; Bayu Dharma Shanti; Vammy Baverly Valentine; Alvin Fadila (International Journal Labs, 2024)
Coronary heart disease (CHD) poses significant risks to health, especially among police officers, a high-risk occupational group due to their demanding work conditions. Factors such as high workloads, occupational stress, poor eating habits, lack of exercise, shift work, and sleep disturbances contribute to CHD risks. This study examined differences in CHD prevalence and risk factors between urban and rural police officers in East Java as part of an evaluation for preventive strategies. A cross-sectional study involving 766 police officers (383 urban, 383 rural) was conducted during 2024 medical check-ups at Bhayangkara State Police Hospital Surabaya. Data collection included physical exams, ECG, treadmill tests, and laboratory analyses of cholesterol and fasting blood sugar. CHD was identified through ischemic ECG changes, treadmill test symptoms, or medical history of cardiac events. Results showed CHD prevalence significantly higher among urban officers (89.7%) compared to rural counterparts (10.3%) (p=0.000). Total cholesterol was significantly associated with CHD risk (p=0.003). These findings highlight the greater vulnerability of urban police officers to CHD, emphasizing the need for proactive prevention strategies. Regular clinical and echocardiographic follow-ups, combined with lifestyle modifications and treatment, are critical to mitigating CHD risks and improving health outcomes for police officers in both urban and rural settings.